Perbandingan Pemahaman Penyusunan Laporan Keuangan Usaha Kecil Menengah Berdasarkan SAK EMKM - Siregar, Rahmah Sudana; Dalimunthe, Ahmad Amin; Hasibuan, Nur Fadhilah Ahmad (Universitas Muhammadiyah Metro, 2023)
The purpose of this study was to determine the understanding of the preparation of financial reports at Gajah Farhan Bakery and UD. Blessing. This study uses a qualitative method with a descriptive approach. The subjects in this study were the business actors of the Gajah Farhan Bakery and UD. Blessings as well as being the object of this research are the financial records of the two business actors. Based on the results of the study, it was shown that the understanding of the preparation of financial reports at Gajah Farhan Bakery's Earloaf Factory was not good, but at UD. The blessing of the understanding of business actors can be said to be good. The two business actors have made financial records but are not in accordance with SAK EMKM. Equation of financial records for the two business actors has also made financial records in the form of cash-in and cash-out bookkeeping as well as debt receipts, receivables and inventories. And the difference between the financial records of the two business actors lies in UD. It is a blessing that makes financial records of the balance sheet and profit and loss, but for the Elephant Earloaf Factory it does not make financial records of the balance sheet and profit and loss.